Physico-chemical characteristics of three saprolites in Peninsular Malaysia - Hamdan, J.; Burnham, C.P. (Taylor and Francis Inc., 1997)
Three highly weathered inland saprolites developed over different parent rocks, namely basalt, granite and schist, were sampled and analyzed for their physico-chemical properties. The profiles were located along new road cuts in Peninsular Malaysia with depth varying from 10 to 26 m deep. The soils in this study were highly weathered, nutrient-poor, and contained large amount of variable charge colloids. They exhibited soil pH (1:2.5, soil:water) below 5.0, and were low in CEC [usually <7 cmol(+)kg-1 soil]. The base saturation was low, but aluminum (Al) saturation was very high with values >70%. All soils had available water content of <100 mm·m-1. The results of the study showed that saprolites were generally unsuitable for the cultivation of perennial crops. Saprolites, which were soft and friable, had poor physical properties and were a poor substrate for agriculture. The available water content was higher than the solum, but would not be accessible to plant roots. The fertility status of the saprolite was poorer than the soil. It had high phosphorus (P)-retention capacity and low net negative permanent charge, and, therefore, had lower cation-retention capacity. The Al phytotoxic effect was lower in the saprolite than the solum.